2019
DOI: 10.1002/pro.3591
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant disorder and high‐affinity zinc binding in the human zinc‐ and iron‐regulated transport protein 4 intracellular loop

Abstract: The human zinc-and iron-regulated transport protein 4 (hZIP4) protein is the major plasma membrane protein responsible for the uptake of zinc in the body, and as such it plays a key role in cellular zinc homeostasis. hZIP4 plasma membrane levels are regulated through post-translational modification of its large, disordered, histidine-rich cytosolic loop (ICL2) in response to intracellular zinc concentrations. Here, structural characteristics of the isolated disordered loop region, both in the absence and prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 82 publications
0
9
0
Order By: Relevance
“…Mechanistically, it is hence possible that the N terminus of nine-TM ZIPs structurally and functionally replaces the distinctly longer and histidine-rich ICL2 of the human members. Noteworthy, all human ZIPs are predicted to share an eight-TM topology, and hence, they lack an intracellular tail, but the ICL2 instead contributes to zinc binding, thereby regulating Zn 2+ transport activity ( 42 , 43 ).…”
Section: Resultsmentioning
confidence: 99%
“…Mechanistically, it is hence possible that the N terminus of nine-TM ZIPs structurally and functionally replaces the distinctly longer and histidine-rich ICL2 of the human members. Noteworthy, all human ZIPs are predicted to share an eight-TM topology, and hence, they lack an intracellular tail, but the ICL2 instead contributes to zinc binding, thereby regulating Zn 2+ transport activity ( 42 , 43 ).…”
Section: Resultsmentioning
confidence: 99%
“…The second conserved histidine-rich segment (region IV) is on the second cytosolic loop connecting TM3 and TM4 (referred to as L2), which is a characteristic feature of many ZIP family members ( Jeong and Eide, 2013 ). It has been shown that the metal chelating residues in the L2 bind zinc with nanomolar affinity ( Bafaro et al, 2015 , 2019 ) and are required for zinc-induced hZIP4 degradation ( Mao et al, 2007 ). However, diminishing zinc binding capability of the L2 by replacing all five histidine residues (H438, H441, H443, H446, and H448) with glycine residues did not affect either endocytosis or zinc sensing ( Figure 2E ), which is consistent with the result of alanine substitution of these histidine residues in hZIP4 ( Mao et al, 2007 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, diminishing zinc binding capability of the L2 by replacing all five histidine residues (H438, H441, H443, H446, and H448) with glycine residues did not affect either endocytosis or zinc sensing ( Figure 2E ), which is consistent with the result of alanine substitution of these histidine residues in hZIP4 ( Mao et al, 2007 ). Because C436 has been indicated to solely confer nanomolar affinity toward zinc ion for the isolated L2 peptide ( Bafaro et al, 2015 , 2019 ), we generated the C436A variant and the C436A/H438G/H441G/H443G/H446G/ H448G variant for which zinc binding at the L2 is supposed to be greatly abrogated and completely eliminated, respectively. As shown in Figures 2F and 2G , no defect in zinc sensing can be detected for these two variants.…”
Section: Resultsmentioning
confidence: 99%
“…The IL2 of HsZIP4 has been extensively studied. The isolated IL2 peptide of HsZIP4 is unstructured as revealed in an NMR study [61] and the highly dynamic nature of the IL2 was also manifested by partial proteolysis of purified full length HsZIP4 [62]. The histidine residues in the IL2 bind zinc ions with nanomolar affinity, and zinc titration in the NMR study showed that, although the IL2 binds two zinc ions, there is no defined manner of zinc‐binding, suggesting that the zinc‐binding sites are highly dynamic and undergoing a fast equilibrium among different conformers [61].…”
Section: Structurementioning
confidence: 99%
“…The isolated IL2 peptide of HsZIP4 is unstructured as revealed in an NMR study [61] and the highly dynamic nature of the IL2 was also manifested by partial proteolysis of purified full length HsZIP4 [62]. The histidine residues in the IL2 bind zinc ions with nanomolar affinity, and zinc titration in the NMR study showed that, although the IL2 binds two zinc ions, there is no defined manner of zinc‐binding, suggesting that the zinc‐binding sites are highly dynamic and undergoing a fast equilibrium among different conformers [61]. These results support the notion that the IL2 functions as a zinc sensor which has been shown to be essential for zinc‐induced endocytic degradation when cells are exposed to tens to hundreds of micromolar of extracellular zinc ions.…”
Section: Structurementioning
confidence: 99%